(untitled) (Journal of Informatics Education and Research, 2025)
The stock market of India consider as one of the most important emerging market in the South Asia, since it has the biggest trading volume among all financial markets in the region, thus the researchers hopes that the results of the study will improve the decisions making of the individual investors through identifying the most important behavioral finance factors, which may affect their decisions when they invest in stocks. Behavioral finance occurs as a result of inefficient markets. Investors that use behavioural finance are more likely to behave irrationally while making decisions. The main objective of this research is to ascertain and empirically demonstrate how mental accounting, regret aversion, and loss aversion behaviour influence investment decisions. An investor’s risk perception as an analysis carries a logical rationale for how investors choose when they are faced with multiple investment choices. I used a questionnaire-based survey method to collect sample data of 300 respondents, Research analysis method using ADF, Correlation and Regression. According to the research conducted, the results of mental accounting, loss aversion and regret Aversion have a significant effect on investment decision in Indian stock market.